2020
DOI: 10.1029/2020ea001165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Roughness Length on WRF Simulated Land‐Atmosphere Interactions Over a Hyper‐Arid Region

Abstract: The aerodynamic roughness length is a crucial parameter that controls surface variables including the horizontal wind, surface temperature, and heat fluxes. Despite its importance, in the Weather Research and Forecasting (WRF) model, this parameter is typically assigned a predefined value, mostly based on the dominant land-use type. In this work, the roughness length is first estimated from eddy-covariance measurements at Al Ain in the United Arab Emirates (UAE), a hyper-arid region, and then ingested into WRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 63 publications
(112 reference statements)
8
26
0
Order By: Relevance
“…They also found that the AOD values were higher in the summer months when the near‐surface wind is stronger. This is in line with other published work (Naizghi & Ouarda, 2016; Nelli et al., 2020a, 2020b).…”
Section: Introductionsupporting
confidence: 94%
“…They also found that the AOD values were higher in the summer months when the near‐surface wind is stronger. This is in line with other published work (Naizghi & Ouarda, 2016; Nelli et al., 2020a, 2020b).…”
Section: Introductionsupporting
confidence: 94%
“…They also found that the AOD values were higher in the summer months when the near-surface wind is stronger. This is in line with other published work (Naizghi & Ouarda, 2016;Nelli et al, 2020aNelli et al, , 2020b.…”
supporting
confidence: 94%
“…Such dust layers are more likely at inland sites where the boundary layer is deeper (Filioglou et al, 2020;Reid et al, 2008), than at coastal sites like Masdar where boundary layer depths are generally below 2 km (Reid et al, 2008;Temimi et al, 2020). The deeper boundary layers inland are caused not only by the higher surface temperatures, but also the increased surface roughness, which leads to a slowdown of the near-surface wind and consequently low-level wind convergence and vertical ascent (Nelli et al, 2020b). Other explanations for these mismatches, as highlighted in (Omar et al, 2013), include differences in the instrument view angle, inhomogeneities in the target region and column, CALIPSO retrieval errors, and detection limits.…”
Section: Methodsmentioning
confidence: 99%
“…As at Hatta, WRF has a tendency to overestimate the strength of the near-surface wind, but F I G U R E 11 As Figure 10 but for 2 m temperature (shading; • C) and 10 m horizontal wind (vectors; m⋅s −1 ) the biases at this station are even more pronounced. The stronger winds in the model have been noted by Fonseca et al (2020), Nelli et al (2020b), Schwitalla et al (2020), and Temimi et al (2020b), and may be explained by a poor representation of its subgrid-scale fluctuations, likely more significant over complex terrain as is the case at the Al Hajar mountains, and/or of the surface drag parametrization. As at Hatta, WRF does not capture the observed cloud cover, is colder at night and takes longer to warm up in the morning, in particular in the GFS runs.…”
Section: Model Evaluation Against In Situ Measurementsmentioning
confidence: 89%
“…(2020b) and Nelli et al . (2020b), where high‐resolution simulations in arid/hyperarid regions were also conducted. In the vertical, 50 levels are considered, more closely spaced in the PBL, with the first vertical level at about 25 m above ground and the model top at 30 hPa.…”
Section: Model Set‐up and Datasetsmentioning
confidence: 99%